Pengawalan kos projek pembinaan oleh kontraktor - Abdul Rahman, Mohamad Sofiuddin (2012)
Cost control in construction project is very important besides the technical knowledge in construction. Poor cost control may lead to reduced profit margin or total loss to the contractor. Making profit is the contractors? main aim when undertaking the project. However good financial and cost control will lead to maximum profit for the contractors? organization. The objectives of this study are to identify the cost control methods used by the contractor in the construction project, to identify the factors considered by the contractor to determine the profit margin and to identify the strategy used by the contractor to reduce the financial risk in the construction project The study is carried out through literature review and questionnaires. The data is analyzed using average index. From the study, the cost control method used by the contractors for monitoring and controlling the cost construction project are using loss or profit based on payment every month method, loss or profit based on payment every completion the element method, loss or profit based on payment after finish every work method, loss or profit based on payment every stage method and loss or profit based on payment after completion of project method. The factors considered by the contractor to determine the profit margin are; the complexity of the project, the risks involved, types of project, inflation, current workload, completion date and competition. The strategy used by the contractor to reduce the financial risk in the construction project are; understanding geographical area, project size depends on financial standing, credit purchasing, prudent management, preparing monthly cash flow, overall planning and continuous project monitoring.